Immediate birth for women between 34 and 37 weeks of gestation with prolonged preterm prelabour rupture of membranes and detection of vaginal or urine group B streptococcus: an economic evaluation. (8th March 2022) - Dietz, Jeremy; Plumb, Jane; Banfield, Philip; Soe, Aung; Chehadah, Fadi; Chang‐Douglass, Stacey; Rogers, Gabriel
Abstract: Objective: What are the costs, benefits and harms of immediate birth compared with expectant management in women with prolonged preterm prelabour rupture of membranes (PPROM) at 34 +0 –36 +6 weeks of gestation and detection of vaginal or urine group B streptococcus (GBS)? Design: Mathematical decision model comprising three independent decision trees. Setting: UK National Health Service (NHS) and personal social services perspective. Population: Women testing positive for GBS with PPROM at 34 +0 –36 +6 weeks of gestation. Methods: The model estimates lifetime costs and quality‐adjusted life years (QALYs) using evidence from randomised trials, UK NHS data sources and further observational studies. Simulated events include neonatal infections, morbidity associated with preterm birth and consequences of caesarean birth. Deterministic and probabilistic sensitivity analyses (PSAs) were performed. Main outcome measures: QALYs, costs and incremental cost‐effectiveness ratio (ICER). Results: In this population, immediate birth dominates expectant management: it is more effective (average lifetime QALYs, 24.705 versus 24.371) and it is cheaper (average lifetime costs, £14, 372 versus £19, 311). In one‐way sensitivity analysis, results are robust to all but the odds ratio estimating the relative effect on incidence of infections. Threshold analysis shows that the odds of infection only need to be >1.5% with expectant management for the benefit of avoiding infections to outweigh the disadvantages of immediate birth. In PSA, immediate birth is the preferred option in >80% of simulations. Conclusions: Neonatal GBS infections are expensive to treat and may result in substantial adverse health consequences. Therefore, immediate birth, which is associated with a reduced risk of neonatal infection compared with expectant management, is expected to generate better health outcomes and decreased lifetime costs. Tweetable abstract: For women with preterm prelabour rupture of membranes and group B streptococcus in vaginal or urine samples, immediate birth is associated with improved health in their babies and reduced costs, compared with expectant management. Tweetable abstract: For women with preterm prelabour rupture of membranes and group B streptococcus in vaginal or urine samples, immediate birth is associated with improved health in their babies and reduced costs, compared with expectant management.